Beyond the traditional oncology patient: the role of palliative care in patients with sickle cell disease receiving stem cell transplantation or gene therapy - Collins, Griffin S.; Levine, Deena R.; Leonard, Alexis; Sharma, Akshay; Johnson, Liza-Marie (Frontiers in Oncology, 2025)
People with severe sickle cell disease (SCD) are now presented with increasing access to curative-intent therapies including allogeneic hematopoietic stem cell transplantation (HCT) and gene therapy (GT). These high-risk, high-reward therapies offer hope for cure and prevention of further injury due to SCD, but they are toxic therapies that carry risk of additional morbidity and mortality. People with severe SCD suffer due to extreme pain and serious multi-system injury which is compounded by the effects of systemic racism. The increasing availability of these complex, sometimes novel, therapies with curative-intent highlights the role for specialist palliative care (PC) in the care of people with severe SCD. Multidisciplinary PC teams employ a holistic, person-centered approach to alleviating suffering by accompanying patients through high-stakes decision making, coping with life-threatening illness, and symptom management. The role for PC beginning early in HCT has been established, though PC is infrequently integrated in HCT. Little research exists regarding the role for PC in care of people with SCD. We present concepts of PC integration for people with SCD undergoing HCT or GT and advocate for PC integration beginning once patients consider a curative-intent therapy throughout the duration and following completion of treatment. As curative-intent therapies for patients with SCD continue to evolve, there is an opportunity for PC, HCT, and SCD teams to collaborate with patients to develop implementable models for high-quality, multidisciplinary care for people with severe SCD and their families.